A Novel Class of Small Molecule Compounds that Inhibit Hepatitis C Virus Infection by Targeting the Prohibitin-CRaf Pathway - Shufeng Liu; Wenyu Wang; Lauren E. Brown; Chao Qiu; Neil Lajkiewicz; Ting Zhao; Jianhua Zhou; John A. Porco Jr; Tony T. Wang (EBioMedicine, 2015)
Identification of novel drug targets and affordable therapeutic agents remains a high priority in the fight against chronic hepatitis C virus (HCV) infection. Here, we report that the cellular proteins prohibitin 1 (PHB1) and 2 (PHB2) are pan-genotypic HCV entry factors functioning at a post-binding step. While predominantly found in mitochondria, PHBs localize to the plasma membrane of hepatocytes through their transmembrane domains and interact with both EGFR and CRaf. Targeting PHB by rocaglamide (Roc-A), a natural product that binds PHB1 and 2, reduced cell surface PHB1 and 2, disrupted PHB-CRaf interaction, and inhibited HCV entry at low nanomolar concentrations. A structure-activity analysis of 32 synthetic Roc-A analogs indicated that the chiral, racemic version of aglaroxin C, a natural product biosynthetically related to Roc-A, displayed improved potency and therapeutic index against HCV infection. This study reveals a new class of HCV entry inhibitors that target the PHB1/2-CRaf pathway.